2005
DOI: 10.12968/ijpn.2005.11.8.19611
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of caring for dying patients which cause anxiety to first year student nurses

Abstract: Findings from the study suggest that it is aspects of the caring role, rather than personal fear of death, that form the source of much of students' anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 35 publications
6
73
0
8
Order By: Relevance
“…The whole process involved in caring for a dying patient, building a relationship with the patient and finally witnessing the same patient lifeless as ❛Caring for a dying patient, building a relationship and witnessing the same patient as a corpse is extremely frightening.❜ a corpse lying in the morgue is extremely frightening and evokes strong emotions. According to Cooper and Barnett (2005), students describe many feelings such as sadness, vulnerability, helplessness and sympathy in their interactions with dying individuals. Such emotional reactions can limit health professionals' ability to care for dying patients effectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole process involved in caring for a dying patient, building a relationship with the patient and finally witnessing the same patient lifeless as ❛Caring for a dying patient, building a relationship and witnessing the same patient as a corpse is extremely frightening.❜ a corpse lying in the morgue is extremely frightening and evokes strong emotions. According to Cooper and Barnett (2005), students describe many feelings such as sadness, vulnerability, helplessness and sympathy in their interactions with dying individuals. Such emotional reactions can limit health professionals' ability to care for dying patients effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students can feel helpless, guilty and distressed while caring for dying patients (Deffner and Bell, 2005). Such emotional reactions limit the professional ability to care for dying patients and make it difficult for students to comprehend the emotional responses of the patients and their families (Cooper and Barnett, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, researchers have suggested that student nurses' first experiences with patient death can have a significant influence on practice, and attitudes regarding death and dying can be firmly established by the time nurses qualify (Chen et al, 2006;Hurtig and Stewin, 1990;Khader et al, 2010). Nurses who find early encounters with death and dying very difficult can experience feelings of inadequacy, helpless, defensiveness or distress and coping mechanisms such as suppression, distancing and avoidance may be adopted (Cooper and Barnett, 2005;Kent, 2004;Terry and Carroll, 2008;Wilson and Kirshbaum, 2011). This can potentially impact on the quality of care delivered, job satisfaction, turnover and attrition.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the inability to prevent death may cause the emergence of different feelings and thoughts in the nursing students, who feel the responsibility of sustaining the life of the individual (Oz, 2004). Some studies on nursing students abroad revealed that students confronted with the death situation during clinical practice, that they had fears about caring a patient with approaching death, and that their training programs failed to prepare them for this situation (Cooper and Barnett, 2005;Shih et al Loftus, 1998). Therefore, as also stated in the literature, the feelings and opinions of nurses about death should be examined from the beginning of their school years, and students should be allowed for being able to express these feelings and develop themselves (Duke, 1997, Macleod et al, 2003, Hurtig and Stewin, 1990.…”
Section: Introductionmentioning
confidence: 99%